Capacity Constraints, Inflation and the Transmission Mechanism : Forward-Looking Versus Myopic Policy Rules - Clark, Peter (IMF Working Papers; Working Paper ;, 1995)
This paper develops a small model of the output-inflation process in the United States in order to examine the implications of alternative monetary policy rules. In particular, two types of policy rules are considered; a myopic rule where interest rates respond contemporaneously to output and inflation and a forward-looking policy rule that exploits information about the nature of transmission mechanism in the setting of interest rates. The model has two key features. First, there are significant lags between interest rates and aggregate demand conditions. Second, the model is based on an asymmetric model of inflation where positive deviations of aggregate demand from potential are more inflationary than negative deviations are disinflationary. As a consequence of this asymmetry, a policymaker that follows a myopic policy rule and allows the economy to overheat periodically will be forced to impose large recessions on the economy to keep inflation under control. The paper shows that the estimated degree of asymmetry implies that myopic policies can result in significant permanent losses in output. By contrast, policymakers that follow a forward-looking policy rule that avoids overheating will not only reduce the variance of output but also raise the mean level of output.